Charter of the City of Portland, Street and Fire Department Laws, Ordinances, Regulations &C., at 225-27, To Regulate The Storage And Sale Of Gunpowder, And Other Explosive Material, §§ 1-10 (1872) - (:unkn) unknown (My University, 1872)
Regulated the keeping and sale of gunpowder
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER